Effects of GABAB receptor activation on spatial cognitive function and hippocampal neurones in rat models of type 2 diabetes mellitus. Issue 1 (19th January 2018) - Cai, Xiao-Jun; Wang, Lei; Hu, Chun-Mei
Abstract : The present study was conducted with the aim being to investigate the effect γ-aminobutyric acid type B (GABAB) receptor activation have on spatial cognitive function and hippocampal neurones found in the rat models of type 2 diabetes mellitus (T2DM). T2DM rat models were then established, randomized, and subsequently assigned into normal control (NC), T2DM, T2DM + chemical grade propylene (CGP), T2DM + baclofen, and T2DM + CGP + baclofen groups. T2DM rats' weight and blood sugar concentrations were monitored. The DMS-2 Morris water maze testing system was performed in order to figure out the spatial cognitive function of these rats. Reverse-transcription quantitative PCR (RT-qPCR) and Western blotting were also performed in order to detect GABAB mRNA and protein expressions. We used the Nissl staining method in order to detect the number of hippocampal neurones, TUNEL (terminal deoxyribonucleotidy transferase-mediated dUTP nick labeling) staining to detect cell apoptosis, and Western blotting method in order to measure the expressions of the apoptosis-related proteins (Bax, cytochrome c (Cyt- c ), Caspase-3, and Bcl-2). In comparison with the T2DM group, the weight decreased, blood sugar concentration increased, and spatial cognitive function as well as hippocampal neurones were both impaired in the T2DM + CGP group, contrary to the rats in the T2DM + baclofen group who showed an opposite trend. The situation in the T2DM + CGP + baclofen group was better than that found in the T2DM + CGP group while proving to be more serious than that of the NC and T2DM + baclofen groups. Conclusively, activating the GABAB receptor improved spatial cognitive function and hippocampal neurones in the T2DM rats.